THE IMPLEMENTATION OF PROJECT-BASED LEARNING IN WRITING DESCRIPTIVE TEXT - Fauziah, Nadia; Karlina Ambarwati, Evi; Putri Utami, Praditya; Ridwan, Iwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Project-Based Learning (PBL) has been widely promoted as an approach that supports meaningful writing instruction in English as a Foreign Language classrooms, yet how teachers actually carried it out in teaching descriptive text remained insufficiently explored through qualitative inquiry. The purpose of this study was to explore how the English teacher applied PBL to the teaching of writing descriptive text. Working within a single Madrasah Tsanawiyah classroom, this qualitative case study traced one English teacher's enactment of PBL across three meetings of a descriptive writing unit on animals, drawing on classroom observation, a semi-structured interview, and students' Canva poster products. The teacher built her cycle around an essential-question stimulus using a familiar visual object, heterogeneous small-group planning, a deliberately time-boxed in-class drafting stage extended into a week-long take-home digital design task, a public presentation paired with peer classification of grammatical elements, and a closing reflective correction session. Findings show this sequence functioned as more than a procedural checklist: it operationalized a socially mediated learning process in which the teacher repeatedly scaffolded students within their zone of proximal development, while peer presentation created accountability that shaped how carefully students composed their sentences. Time pressure on digital design was the main structural constraint, resolved by shifting that stage outside class hours. The study concludes that effective PBL implementation rests less on strict fidelity to a fixed model than on a teacher's situated, adaptive translation of its core elements into workable classroom decisions.